2011
DOI: 10.1111/j.1365-2702.2010.03537.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the Turkish version of the Pediatric Symptom Checklist‐17 for detecting psychosocial problems in low‐income children

Abstract: Primary care providers can use the Pediatric Symptom Checklist-17 for early identification of childhood psychosocial problems in primary care settings. This easy-to-use tool can provide guidance to care providers for further assessment of children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 27 publications
0
10
0
11
Order By: Relevance
“…ROCC analyses suggested lower cutoff scores than those currently suggested with the PSC-17 total score (i.e., 15). It was noted that an overall cutoff score of 12 was identified in other PSC-17 studies for older children in primary care settings (Erdogan & Ozturk, 2011; Stoppelbein, Greening, Moll, Jordan, & Suozzi, 2012). The results appear reasonable as young children’s observed behaviors may differ from older children in the original sample of the measure, and age differences should be considered in future cutoff score validation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…ROCC analyses suggested lower cutoff scores than those currently suggested with the PSC-17 total score (i.e., 15). It was noted that an overall cutoff score of 12 was identified in other PSC-17 studies for older children in primary care settings (Erdogan & Ozturk, 2011; Stoppelbein, Greening, Moll, Jordan, & Suozzi, 2012). The results appear reasonable as young children’s observed behaviors may differ from older children in the original sample of the measure, and age differences should be considered in future cutoff score validation.…”
Section: Discussionmentioning
confidence: 97%
“…While the PSC-17 had been previously validated and successfully used in primary care settings with parent raters (e.g., Blucker et al, 2014; Chaffin et al, 2017; Erdogan & Ozturk, 2011; Gardner, Lucas, Kolko, & Campo, 2007; Murphy et al, 2016), additional research is needed to examine the psychometric properties of a measure before extending the use of the scale (AERA, APA, & NCME, 2014, Standard 1.4) to school-based settings. Until now, only one study has been conducted to examine the content validity and validate the factor structure of the PSC-17 for preschool children with teacher ratings (DiStefano et al, 2017).…”
Section: The Psc-17 As a Universal Screening Toolmentioning
confidence: 99%
“…Among low-income children in Turkey, a positive rate of nearly 40% was recorded using the PSC-17. 25 Among Brazilian schoolchildren, the PSC-positive rate was 14%. 18 In the United States, a study of some 21,000 children found a PSC-positive rate of 13% among school-age children 20 ; a previous study among low-income US children documented a positive rate of 22%.…”
Section: Discussionmentioning
confidence: 99%
“…Bu nedenle davranış sorunlarına zamanında müdahale büyük önem taşı-maktadır. Yapılan çalışmalar erken müdahale ile erişkin yaşamdaki risklerin azaltılabileceğini vurgulamaktadır (53)(54)(55)(56)(57) .…”
Section: Davranışsal Sorunlarda Müdahale Yöntemleri Ve Psikiyatri Hemunclassified
“…Davranış sorunlarının gelecekte kalıcı şekilde kişilik ve uyum sorunlarına yol açtığı göz önünde bulundurulduğunda çocuk yaşta bu sorunların halledilmesinin önemi ortaya çıkmaktadır (4,31,(53)(54)(55)(56)(57) . Davranış sorunlarıyla mücadele etmede bütüncül bir bakış açısı benimsenebilir.…”
Section: Sonuçunclassified